New species of Laxotela Winterton & Irwin from Australia (Diptera: Therevidae: Agapophytinae) - Winterton, Shaun L. (Zootaxa, 2007)
Two new species of the endemic Australian stiletto fly genus Laxotela Winterton & Irwin are described and figured. Laxotela elongata sp. nov. is described from Queensland while Laxotela plata sp. nov. is described from south-eastern mainland Australia. Laxotela ornata (Kröber) comb. nov. (originally Spatulipalpa Kröber) was recently placed as incertae sedis within Therevidae, but is herein transferred to Laxotela. A revised key to Laxotela species is presented.